Pengaruh Price, Service Qality Dan Marketing Online Terhadap Keputusan Pembelian Di E-Commerce Shopee (Studi Kasus Pada Kaum Generasi Z Di Kota Malang) - Galih Dewa Nabilla Hafidh; Jeni Susyanti; Eris Dianawati (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This research was conducted to investigate how purchasing decisions are affected by price, service quality, and online marketing at E-commerce Shopee. The data was obtained by distributing questionnaires to Generation Z in Malang city which were selected using the purposive sampling method and the number of samples was determined using the Maholtra formula and the results obtained were 90 respondents. In this study, IBM SPSS V.25 for Windows was utilized for data analysis. The validity test, reliability test, normality test, classical assumption test, multiple linear regression test, hypothesis test, and coefficient of determination are among the data testing methodologies employed in this study. The results of this study indicate that Price has a significant effect on Purchasing Decisions, Service Quality has a significant effect on Purchasing Decisions, and Online Marketing has a significant effect on Purchase Decisions. Keywords: Price, Service Quality, Online Marketing, Purchasing Decisions.